Polyaniline and iron based catalysts as air cathodes for enhanced oxygen reduction in microbial fuel cells. Issue 97 (21st October 2015) - Tang, Xinhua; Li, Haoran; Du, Zhuwei; Ng, How Yong
<x xml:space="preserve">Abstract</x> Iron–nitrogen–carbon catalysts exhibited very high catalytic activity towards ORR and significantly enhanced power production in MFCs.